PENYEBARAN TATA LETAK TRADISIONAL STREET FOOD DI KOTA GORONTALO - Zees, Dewi Sartika; Moha, Devie Indriany; Akbar, La Ode Juni (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2023)
Culinary has become a part of the socio-economic life of the people in the city of Gorontalo. Immigrants who are visiting the city of Gorontalo are mostly definitely looking for places to eat that are in great demand by the public. While in Gorontalo City, culinary is also the biggest destination for Gorontalo residents who migrate to other places. Culinary tours such as traditional street food and modern food are starting to line up a lot along the streets of Gorontalo city. However, Gorontalo City has 3 problems in the tourism sector, especially in its culinary tourism potential. The first problem is the lack of complete facilities and good quality infrastructure at street food locations in Gorontalo City for both sellers and buyers. In other words, the location and layout of street food in Gorontalo City is still random and not neatly organized. The second problem is that tourism promotion is still not maximal in highlighting Gorontalo's special food and drinks or efforts to introduce traditional flavors of street food in a unique way are still very minimal. In addition, there is a lack of effective coordination between tourism associations and the local government in paying attention to the location of street food businesses in Gorontalo City. Therefore, improvements in various aspects must be made to improve the development of traditional street food places in the city of Gorontalo like other regions in Indonesia and other countries which can be used as examples of success in realizing culinary tourism with the theme of traditional food as regional icons that can help in increasing regional economy and preserving cultural heritage in the form of typical food and drink from the area.